Individual determinants of primary healthcare utilisation in Gaza Strip, Palestine. Issue 8 (11th July 2008) - Abu-Mourad, T; Alegakis, A; Shashaa, S; Koutis, A; Lionis, C; Philalithis, A
Abstract : Objectives: To examine the extent to which primary care patients are using the primary healthcare (PHC) services in Gaza Strip, Palestine, and to determine the factors that are associated with the use of these services. Methods: Using Andersen's behavioural model, the authors interviewed 956 PHC attendees. Patients were questioned about predisposing factors: age, sex, marital status, education, work status, household size, life events (psychological and financial), perceived living conditions and health locus of control. Enabling factors included urbanisation and household income. Need factors included self-rated health. Healthy lifestyle was measured by two variables: smoking and physical activity. Outcome factors were measured by patients' satisfaction with PHC. Results: The study revealed that the majority of interviewed patients (64.7%) reported high use (>3 times per 6 months) of PHC within the 6-month period before the interview. The main factors found to be associated with high use of PHC were older age, married and divorced/widowed status, perceived bad living conditions, not working, high level of income, poorly rated health status and current smoking habit. Conclusions: Gazean primary care patients are high users of PHC services. The increased use of these services is associated with the basic predisposing, enabling and needs factors and with the unique bad living conditions. Tobacco use was another aspect associated with high use of PHC. Effective health management, based on promoting a healthy lifestyle, is needed. The findings of this study can be used to improve health service planning and guide decision-makers towards healthcare resource allocation according to healthcare needs.